2017
DOI: 10.1146/annurev-animal-022516-022928
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Petroleum-Derived Pollutants on Fish Development

Abstract: The teleost fish embryo is particularly sensitive to petroleum hydrocarbons (polycyclic aromatic hydrocarbons, PAHs) at two distinct stages of development. The first is early during cleavage stages when PAHs alter normal signaling associated with establishment of the dorsal-ventral axis. This disruption involves the Wnt/β-catenin pathway and results in hyperdorsalized embryos that do not survive to hatching. The second, more sensitive period is during heart development, when oil and PAHs cause abnormal develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 112 publications
1
29
0
Order By: Relevance
“…PAHs can dysregulate ß-catenin, a key component of the Wnt pathway, leading to patterning defects in zebrafish and Pacific herring 52 . Wnt signaling is important for early cardiac development, and cardiac dysfunction is a major outcome of PAH toxicity 14 , 61 , 62 . It is unclear if the cardiac defects in PAH-exposed embryos are partially due to disrupted Wnt signaling; several studies demonstrate that PAHs act through the aryl hydrocarbon receptor (AHR) to cause cardiotoxicity 15 , 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs can dysregulate ß-catenin, a key component of the Wnt pathway, leading to patterning defects in zebrafish and Pacific herring 52 . Wnt signaling is important for early cardiac development, and cardiac dysfunction is a major outcome of PAH toxicity 14 , 61 , 62 . It is unclear if the cardiac defects in PAH-exposed embryos are partially due to disrupted Wnt signaling; several studies demonstrate that PAHs act through the aryl hydrocarbon receptor (AHR) to cause cardiotoxicity 15 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling is important for early cardiac development, and cardiac dysfunction is a major outcome of PAH toxicity 14 , 61 , 62 . It is unclear if the cardiac defects in PAH-exposed embryos are partially due to disrupted Wnt signaling; several studies demonstrate that PAHs act through the aryl hydrocarbon receptor (AHR) to cause cardiotoxicity 15 , 61 . AHR activation may cause cardiotoxicity in zebrafish by downstream disruption of Wnt signaling, suggesting that Wnt could play a central role in developmental stormwater toxicity 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The teleost fish embryo is particularly sensitive to PAHs at two distinct stages of development [33]. The first is early during the cleavage stages when PAHs alter the normal signaling associated with the establishment of the dorsal-ventral axis.…”
Section: Toxicity Of Pahs On the Early Development Of Fishmentioning
confidence: 99%
“…PAHs are considered carcinogenic chemicals and are concerning as they are important organic pollutants in the environment and human society ( Figure 1). Moreover, additional toxicological studies have revealed other types of toxicities from PAHs: developmental toxicity, genotoxicity, immunotoxicity, oxidative stress, and endocrine disruption [32][33][34][35][36]. Because of their ubiquity in the natural environment and various harmful effects on organisms, PAHs are among the most concerning organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, globally ubiquitous industrial pollutants such as dioxin-like chemicals (DLCs) may disrupt cardiovascular and craniofacial development in vertebrate embryos (King-Heiden et al, 2012), and in adults may cause immune system, liver, and skin toxicity, reproductive dysfunction, and cancer (Denison, Soshilov, He, DeGroot, & Zhao, 2011). Similarly, some polycyclic aromatic hydrocarbons (PAHs), which are common toxicants in combustion pollutants and crude oil, can cause developmental defects in embryos (Barron, Carls, Heintz, & Rice, 2004;Cherr, Fairbairn, & Whitehead, 2017), and immune system toxicity, oxidative stress, endocrine disruption, and cancer in adults (Hylland, 2006). Deliberately designed poisons tend to have discrete mechanisms of acute biological effect, with distinct molecular targets, so that adaptive phenotypes may be simple.…”
Section: Chemical Complexity and Dimensionality Of The Adaptive Phementioning
confidence: 99%